Evolutionary processes and organizational adaptation : a Mendelian perspective on strategic management - Levinthal, Daniel A. (Oxford : Oxford University Press, 2021)
How do firms adapt? Is it through rational choice and intentionality, or rather a process of evolutionary dynamics? Using the ideas of Gregor Mendel as a touchstone, this book constructs a middle-ground between these two conceptions and provide a new framework for understanding the adaptive dynamics of organizations.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on June 7, 2021).
Keywords: Organizational change; Management